Effect of denture fabrication and wear on closest speaking space and interocclusal distance during deglutition - Freitas de Souza, Raphael; Marra, Julie; Pero, Ana Carolina [UNESP] [UNESP]; Compagnoni, Marco Antonio [UNESP] (Elsevier B.V., 2007)
Statement of problem. The accuracy of assessing maxillomandibular relationships for trial bases and dentures using phonetic and swallowing methods has not been compared to that observed with definitive prostheses. Thus, there is no evidence to prove whether measurements obtained through such methods remain the same after adaptation to dentures.Purpose. This study investigated changes in the closest speaking space, interocclusal rest space, and interocclusal distance during deglutition in edentulous patients during and after complete denture treatment.Material and methods. Eighteen edentulous subjects participated in this study and measurements were performed after 7 Intervals of time: (1) with occlusion rims and record bases following creation of the maxillomandibular relationship record, (2) with trial dentures, (3) at Insertion of definitive complete dentures, (4) 1 week, (5) 2 weeks, (6) 1 month, and (7) 3 months after insertion. Recordings of interocclusal distances were made with a mandibular kinesiograph. Closest speaking space was measured during the pronunciation of the word 'seis'. The distance between postural rest position and centric occlusion, or interocclusal rest space, was measured using a kinesiograph. Interocclusal distance during deglutition was tested by recording the closest mandibular position recorded during swallowing of 20 mL of water. Data were analyzed using repeated-measure ANOVA, followed by the Student-Newman-Keuls test (alpha=.05).Results. A significant (P <.01)reduction in the mean closest speaking space was found when it was evaluated using occlusion rims and record bases (4.6 mm) compared with other stages (3.0 to 3.4 mm). No significant differences were found in mean interocclusal rest space and interocclusal distance during deglutition among the time periods evaluated.Conclusions. The presence of occlusion rims can influence mandibular position during pronunciation of the /s/ sound. The arrangement of artificial teeth changes the closest speaking space. However, rest position and deglutition were not affected, either during denture fabrication or short-term use.